2002
DOI: 10.1590/s0034-72992002000300014
|View full text |Cite
|
Sign up to set email alerts
|

Infecções dos espaços cervicais: estudo prospectivo de 57 casos

Abstract: destas apresentaram flora mista. Os microorganismos mais prevalentes dentre os aeróbicos foi o Streptococcus viridans (41,5%) e, dentre os anaeróbios, Peptostreptococcus micros e Peptostreptococcus sp (5,7% e 3,8%, respectivamente). A associação entre penicilina cristalina e metronidazol foi o tratamento preconizado em 31 pacientes (54,3%). Nos demais, diversos antibióticos como clindamicina, cefalosporinas de terceira geração, cloranfenicol e oxacilina foram utilizados. Cinqüenta e quatro pacientes (94,7%) ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Brito et al also found that descending mediastinitis was the commonest complication in multispace neck abscesses. 10 Tracheostomy was done in the cases of Ludwig's angina in our study to alleviate the upper airway obstruction like in the studies by Brito et al and Har-El et al 10,24 Most of the abscesses had upper respiratory tract infection (32.2%) and dental pathology (27.6%) as the origin of abscess in our study whereas dental focus was higher (37%) than upper aero-digestive tract infection (20%) in a study done by Coelho et al 25 and Sennes et al 26 Diabetes mellitus was seen as an associated systemic disorder in our study which was similar to the other studies. 3,19 Whereas cardiopulmonary diseases were more prevalent as a co-morbid condition in a study done by Kauffmann et al 2 The microbiology of the deep neck abscess varies with the space involved.…”
Section: Discussionsupporting
confidence: 74%
“…Brito et al also found that descending mediastinitis was the commonest complication in multispace neck abscesses. 10 Tracheostomy was done in the cases of Ludwig's angina in our study to alleviate the upper airway obstruction like in the studies by Brito et al and Har-El et al 10,24 Most of the abscesses had upper respiratory tract infection (32.2%) and dental pathology (27.6%) as the origin of abscess in our study whereas dental focus was higher (37%) than upper aero-digestive tract infection (20%) in a study done by Coelho et al 25 and Sennes et al 26 Diabetes mellitus was seen as an associated systemic disorder in our study which was similar to the other studies. 3,19 Whereas cardiopulmonary diseases were more prevalent as a co-morbid condition in a study done by Kauffmann et al 2 The microbiology of the deep neck abscess varies with the space involved.…”
Section: Discussionsupporting
confidence: 74%
“… 26 Sennes found Streptococcus viridans in 41.5% of the cases, Staphylococcus aureus in 20.7% of them, and 3.8% with Haemophilus influenza . 14 In our study, Streptococcus pyogenes was the most frequently detected agent (23.3%), which can be explained by the higher incidence of peritonsillar infections. From all patients, 14.5% showed no growth of bacteria in culture, which can be explained by the use of high doses of intravenous antibiotics before abscess surgical drainage.…”
Section: Discussionmentioning
confidence: 53%
“…In a study by Coelho et al, dental focus was the origin of abscesses in 37% of patients, whereas pharyngeal tonsil and disorders were present in 20% of cases, not being possible to identify the source of infection in 33% of patients. 13 To Sennes et al, odontogenic infection was the cause in 42.1% of patients, tonsillitis in 17.5%, post upper airway infections in 15.8% and unknown cause in 8.8% 14 lymphadenitis. Among other causes, post upper airways infection, lymphadenitis and foreign body ingestion were still found in 17.8% of cases, adenitis (submandibular and parotid) at 7.8% and 39.6% in the fasciitis.…”
Section: Discussionmentioning
confidence: 98%
“…Certos autores advogam intervenção cirúrgica precoce mesmo nos casos em que os achados clínico-tomográfi cos sejam compatíveis com celulite, sem coleção purulenta. Outros autores como Topazian e Goldberg (apud MARZOLA; PASTORI, 2006), e também Sennes et al (2002) e Lorenzo et al (2006) ainda defendem uma conduta mais tradicional, optando pela drenagem, quando o abscesso apresentar um ponto de fl utuação, evidências de liquefação em meio aos tecidos, antes da ruptura espontânea. O paciente deve ser avaliado o mais rápido possível, sendo a drenagem realizada na presença de sinais clínicos signifi cantes.…”
Section: Tratamento Cirúrgicounclassified